Garden Smellscape–Experiences of Plant Scents in a Nature-Based Intervention - Pálsdóttir, Anna María; Spendrup, Sara; Mårtensson, Lennart; Wendin, Karin (Frontiers in Psychology, 2021)
This study explores how participants suffering from stress-related mental disorders describe their perception, interaction, and lived experience of garden smellscape during their nature-based rehabilitation. Natural elements, and especially nature smells, have been found to have a profound effect on stress reduction, suggesting an interesting link between odor in nature and stress reduction. The study was conducted as a longitudinal case-study, running over a period of 5 years, investigating participants’ perceptions of a garden smellscape, after completing a 12-weeks nature-based rehabilitation in Alnarp Rehabilitation Garden, Sweden. All participants were treated for stress-related mental disorders. Data were collected through retrospective semi-structured individual interviews and analyzed according to interpretative phenomenological analysis. The results revealed in what way nature odor (odor in nature) evoked associations, emotions, and physical reactions and provide examples of how nature scents function as a catalyst for sensory awareness and memories. Findings supported the understanding that experiencing the smell of plants, especially pelargonium, may facilitate stress reduction and support mental recovery in a real-life context. The results of the study can be used for several purposes; thus, they are relevant for actors within the development of nature-based therapy, as well as stakeholders within the horticultural industry.